Encrypted Negative Password in Real Time - G.K.Sandhia, Karthik Narayan V (International Journal of Advanced Science and Technology, 2020)
Secure secret phrase stockpiling is an indispensable angle in frameworks in light of secret word verification, which is as yet the most broadly utilized verification strategy, even though there are certain constraints leading to reduced security within the system. In this paper, we propose a secret word verification system that is intended for secure secret word stockpiling and could be effectively incorporated into existing confirmation frameworks. In our structure, first, they got plain secret phrase from a customer is worked out a cryptographic hash work. At that point, the hashed secret phrase is changed over into a negative secret key. At long last, the negative secret key is scrambled into an Encrypted Negative Password utilizing symmetric-key calculation and an added layer of security could be worked in using multi-cycle encryption. The use of this combination of hashing and symmetric encryption increases the difficulty in obtaining passwords from ENPs. There are ‘n’ ENPs for any given non complex secret key, which makes precipitation assaults in-feasible. The calculation intricacy investigations and examinations demonstrate that the ENP could oppose query table assault and give more grounded secret key insurance under word reference assault. ENP has its limitations and can be inferred as a single use algorithm. Although, in reality the combination of ENP with certain algorithms can lead to the creation of an extremely strong encryption algorithm that would be able to stay strong against several attacks.